Soret and Dufour effects on viscoelastic boundary layer flow over a stretching surface with convective boundary condition with radiation and chemical reaction - Eswaramoorthi, S.; Bhuvaneswari, M.; Sivasankaran, S.; Rajan, S. (Sharif University of Technology, 2016)
In this article, we investigate the double diffusive ow of a viscoelastic uid on a stretching paper with convective boundary condition under the inuence of thermal-diffusion and diffusion-Thermo effects, thermal radiation, internal heat generation or absorption, chemical reaction, and thermal radiation. The governing boundary layer equations are analytically solved by using Homotopy Analysis Method (HAM). Variations of the velocity, concentration, and temperature profiles for different values of physical parameters are graphically displayed and discussed. Numerical results of the local Sherwood number and the local Nusselt number are also tabulated. It is observed that the local Nusselt number increases on increasing the radiation parameter. The local Sherwood number increases on increasing the chemical reaction parameter.